Estrés y desempeño laboral alcanzado por los trabajadores administrativos de la red de salud Ilo post confinamiento a causa del coronavirus 2021 - Manihuari Amias, Henrry (2022)
The objective of this thesis was to determine the relationship between stress and job performance achieved by administrative workers of the Ilo Health Network post confinement due to coronavirus 2021, the type of study that I opted for was applicative, under a descriptive correlational level and non-experimental design; I include as a population 20 administrative workers of the ILO Health Network, to whom the survey technique and the questionnaire as an instrument were applied. According to the results, it was established that the level of stress reached was of a high average (40%) since the entity sometimes lacks direction and objective; furthermore, that he never feels uncomfortable working with members of other work units; Also, your team is never disorganized. On the other hand, the level of work performance is considered medium (30%) because the work sometimes exceeds the planned expectations; then, they almost always have the necessary knowledge for the efficient fulfillment of their functions. To conclude, the relationship between stress and job performance is considerable negative, with a coefficient and a significance (r=-0.861, p=0.01).